Case Report: Common variable immunodeficiency phenotype and granulomatous–lymphocytic interstitial lung disease with a novel SOCS1 variant - Caldirola, María Soledad; Daiana, Espantoso; Gomez Raccio, Andrea Cecilia; García, Ana Luz; Bernacchia, Agustin; Medín, Martín; Gaillard, Maria Isabel; Di Giovanni, Daniela (Frontiers in Pediatrics, 2024)
Common variable immunodeficiency is a heterogenous symptomatic group of inborn errors of immunity that mainly affects antibodies production and/or function, predisposing patients to recurrent and severe infections. More than half of them usually develop autoimmunity, lymphoproliferation, enteropathy and malignancies. Among these conditions, chronic lung disease such as granulomatous lymphocytic interstitial lung disease is one of the leading causes of death in these patients. During recent years, many genes that play a key role in B and T cells development, maintenance and/ or cytokines signaling pathways have been implicated in the pathogenesis of the disease. Here, we describe the first Argentinian patient presenting with common variable immunodeficiency and granulomatous lymphocytic interstitial lung disease, harboring two in cis heterozygous variants in SOCS1 gene.